Extraction and purification of papain obtained from three native species of the genus Vasconcellea - Rivera-Botonares, Ralph Stein (2023)
In this research, the papain enzyme was obtained from the latex of three species of the Vasconcellea genus, V. chachapoyensis, V. heilbornii and V. pubescens, species native to the Amazon region in Peru. The extracted latex was conditioned with sodium acetate buffer, EDTA and sodium bisulfite solution. The purification was carried out adapting the method of Andrade (2011), ammonium sulfate was used for precipitation; 96° ethanol in two stages for dilution; the pH was regulated at 6.0 and 8.0 with NaOH 0.1 N, it was centrifuged in three stages; frozen at -65 °C for 12 hours; and lyophilized from 24 to 36 hours with a vacuum of 0.1 to 0.6 mbar and a collector temperature of -84 to -85 ° C, finally it was packed in dark bottles. Using the milk coagulation method (Balls and Hoover) the enzymatic activity (AE) was determined, the three species obtained higher values of AE at pH 6.0 than at pH 8.0; V. chachapoyensis presented a higher significant average of EA (240.97 Upe), followed by V. pubescens (195.80 Upe) and V. heilbornii (112.45 Upe), it was also significantly higher than commercial papain (208.14 Upe). V. pubescens had higher proteolytic activity than the other species.